Psy-Warriors - Clarke, Alan; Westbury, Ken; Ayres, Rosalind; Bate, Anthony; Blakely, Colin (bfi, 2016)
Originally written in 1978 for the theatre, it was inspired by Peter Watson’s book "War on the Mind: the Military Uses and Abuses of Psychology", and looks at the ethics of torture, asking how far society can torture and degrade prisoners in the name of democracy and freedom, flipping the situation somewhat by having a group of soldiers captured by terrorists. As well as the Northern Ireland issue, the play also considers Palestine and equally controversially included footage of an actual killing, as well as drawing from official reports and research into the physical and mental treatment of terrorist suspects. [www.the-medium-is-not-enough.com]
Keywords: Blu-Ray-Disc